The effects of two different dietary regimens during exercise on outcome of experimental acute kidney injury - Nazanin Sabet; Zahra Soltani; Mohammad Khaksari; Alireza Raji-Amirhasani (BMC, 2022)
Abstract Background Acute kidney injury (AKI) is a syndrome characterized by rapid loss of excretory function of kidney. Both exercise and some diets have been shown to increase silent information regulator (SIRT1) expression leading to reduction of kidney injury. In this study, the effect of two different diets during exercise on kidney function, oxidative stress, inflammation and also SIRT1 in AKI was investigated. Materials and methods A number of rats were randomly divided into four groups; control without exercise, control with exercise, exercise + calorie restriction (CR), and exercise + time restriction (TR). Each group was divided into two subgroups of without AKI and with AKI (six rats in each group). Endurance exercise and diets were implemented before AKI. Serum urea and creatinine, urinary albumin, kidney malondialdehyde (MDA), total antioxidant capacity (TAC), transforming growth factor (TGF-β1), and SIRT1 levels, glomerular filtration rate (GFR) and relative kidney weight were measured before and 24 h after AKI induction. Results After induction of kidney injury, serum urea and creatinine, urinary albumin, kidney MDA and TGF-β1 levels increased in rats with both previous exercise and no previous exercise, while GFR, and kidney TAC and SIRT1 levels significantly decreased. These changes after AKI were less in the group with previous exercise than in the group that had no exercise (p <0.001). The TR diet during exercise caused a less increase in serum urea (p <0.01) and creatinine (p <0.01), and urinary albumin (p <0.001) levels after the injury compared to the just exercise group. Also, both CR and TR diets during exercise caused less change in MDA (p <0.001) and TAC (p <0.05, p <0.001, respectively) levels compared to just exercise group. Conclusions The results showed that exercise alone had no effect on preventing function impairment of kidney, oxidative stress, inflammation and also SIRT1 alteration following AKI, although these indexes were less among those with exercise than those without exercise. However, when the CR and TR diets were implemented during exercise, strong renoprotective effects appeared, and the protective effect of TR diet was greater.